The strategic recovery of the insurance service and its reflection on achieving the strategic goals: research My application in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research topic dealt with the strategic recovery of the insurance service, which is one of the approaches that have an important role in providing solutions and remedies for the recession that affects companies and hinders them from achieving their strategic goals. The research also addressed the strategic objectives of the company as the rationale and actual guide for companies of all activities in order to protect their systems from deviation for its desired purpose. So the aim of the research is to demonstrate the repercussions of the strategic recovery of the insurance Service represented by (compensation, speed of response, apology, initiative (identifying the problem). The company's strategic goals are represented (profitability, growth, employee satisfaction, community service) in the National Insurance Company, and the questionnaire has been approved As a tool to collect data and information from the sample of (58) who are in (department manager, M. department manager, division official, unit official), and the statistical program (spss) was used to calculate (standard deviation, mean, difference factor, determination factor (R2), f test, x2 test) and the research reached a number of conclusions, the most prominent of which were: - There is an effect of the strategic recovery of the insurance service in achieving the strategic goals amounted to (57%), and there are significant differences in the sample response around the questionnaire paragraphs according to personal variables ( Age, educational qualification, job position, number of years of service), in addition to the level of the sample response to the importance of the strategic recovery of the insurance service and achieving the strategic goals in a high degree.